2022
DOI: 10.1039/d2gc01983c
|View full text |Cite
|
Sign up to set email alerts
|

Halometallate ionic liquids: thermal properties, decomposition pathways, and life cycle considerations

Abstract: Halometallate ionic liquids provide new opportunities for industrial catalytic processes because of their unique blend of physical and chemical properties. Tunability underpins the success of ionic liquids because small structural...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…Similar thermal properties were observed for imidazolium-based MILs including zinc and nickel. Here, Clarke et al 34 show a crystallization there is one example, IL 2, which does not show a direct crystallization signal. Also T g is not always observed upon cooling.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…Similar thermal properties were observed for imidazolium-based MILs including zinc and nickel. Here, Clarke et al 34 show a crystallization there is one example, IL 2, which does not show a direct crystallization signal. Also T g is not always observed upon cooling.…”
Section: Resultsmentioning
confidence: 80%
“…Similar thermal properties were observed for imidazolium-based MILs including zinc and nickel. Here, Clarke et al 34 studied the thermal properties and stability of multiple MILs consisting of different metal halide anions and imidazolium or phosphonium-based cations. As shown here, the MILs presented by Clarke et al are all thermally stable up to 200 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Finally yet importantly, this last study was limited to simple, metal-free anions. The case of halometallate anions, and more specifically chloroferrate anions, , is more complex as it involves anion speciation and dynamic equilibria with monomeric and/or oligomeric anionic species of varying nuclearity and coordination numbers. , Although essential for providing intermediate Lewis acidity and relatively high thermal stability, the role of the chloroferrate anion is still open to debate. A systematic investigation of the composition and physicochemical properties of 1-alkyl-3-methylimidazolium chloroferrate ILs has never been proposed in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Ionic liquids (ILs) are a type of efficient green solvent and organic functional material developed in recent years, and are widely used in the separation of biomass materials and the preparation of various advanced functional materials because of their low pressure, high thermal stability, strong solubility and easy recovery. 1,2 Back in 2002, Rogers and his co-workers found that some ILs could dissolve cellulose via microwave heating. 3 Recently, much progress has been made in the research on ILs for the dissolution and separation of biomasses such as lignin and cellulose.…”
Section: Introductionmentioning
confidence: 99%